2019
DOI: 10.30837/2522-9818.2019.9.072
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Computer Network Load Parameters Over a Given Period of Time

Abstract: Innovative technologies and scientific solutions for industries. 2019. No. 3 (9)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…1). When considering the transport layer of the OSI model, it should be noted that the transport layer provides data transportation services [28]. In particular, the primary purpose of the transport layer is to address issues such as ensuring reliable transport of data through a unified network.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). When considering the transport layer of the OSI model, it should be noted that the transport layer provides data transportation services [28]. In particular, the primary purpose of the transport layer is to address issues such as ensuring reliable transport of data through a unified network.…”
Section: Methodsmentioning
confidence: 99%
“…Article [28][29][30] identified the main characteristics of a computer network that have an impact on data transmission processes, and proposed a method for formalizing metrics that are directly applicable in the modeling process. The following network characteristics were considered:  bandwidth;  delays in communication channels;  quality of service;  the extent of transmission errors.…”
Section: Highlighting Previously Unsolved Parts Of a Common Problem mentioning
confidence: 99%
“…Measurements of the generated and distributed network traffic enabled statistical descriptions and parametric descriptions in [ 4 , 5 , 8 ]. In recent work [ 3 , 6 , 7 , 9 , 10 , 11 , 12 , 13 ], statistical typification of network traffic with known distribution functions and parameter variation was defined or the traffic was described by using self-similarity related to heavy-tail distributions [ 14 , 15 ]. Further definitions of network traffic were limited to the recognition network traffic type (voice internet, HTTP, VoIP, multimedia, etc.)…”
Section: Related Workmentioning
confidence: 99%
“…Much attention is paid to the study of factors that affect the quality of service (QoS) of computer networks. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Studies of the influence of data transmission channel throughput were conducted in [1][2][3][4].…”
Section: Literature Analysismentioning
confidence: 99%
“…№ 1 (11) ISSN 2524-2296 (online) between QoS indicators and meeting the requirements for computer system transactions [15][16][17][18][19][20]. In [21], the main parameters of the basic telecommunications network that affect the quality of transaction execution of a computer system are highlighted. In particular, it is shown that when choosing special platforms with centralized management (converged and hyperconverged), synchronization of the computer system plays a significant role.…”
Section: Literature Analysismentioning
confidence: 99%